Design, implementation and experimental verification of a compensator-based triple-step model reference controller for an automotive electronic throttle. (July 2020) - Gao, Jinwu; Feng, Kai; Wang, Yulei; Wu, Yuhu; Chen, Hong
Abstract: The electronic throttle of a gasoline vehicle controls the air inflow into the cylinders of the engine to ensure the desired power output. Therefore, a well-established electronic throttle control (ETC) system is fundamental and necessary to obtain fast transient engine torque responses without overshoot and with high static precision. To achieve highly precise servo control of the throttle in an environment with system nonlinearity, model uncertainties and external disturbances, a discrete-time triple-step model reference controller (DT-TSMRC) with an adaptive compensator is proposed for an ETC system. In contrast to previously investigated systems, the proposed controller consists of steady-state control, reference feedforward control, proportional-derivative (PD)-type feedback control, and an online updating compensation law. Experimental results show that the proposed control algorithm can not only ensure fast transient performance in the control response without overshoot but also guarantee accurate servo tracking of the valve plate angle. Highlights: Novel DT-TSMRC method is proposed for the electronic throttle control problem. The proposed adaptive compensator accounts for all system mismatch and disturbances. The proposed error feedback controller is extended to the classic PD structure. Experimental tests validate the performance of the proposed control system.